How a catchy bass line might someday resonate beyond my business ethics classroom: Rock music in management learning. Issue 2 (April 2021) - Michaelson, Christopher
Business ethics is one of the "unsettled humanities" in a management curriculum that tends to value instrumental and measurable goods. However, the value of business ethics may not be apparent to students until they experience unpredictable challenges to their ethical values at work long after they have left the management classroom. This essay traces my journey to using music – particularly, British rock songs – to reinforce learning and retention of the essential feelings and ideas in my students' learning experience. It draws upon contrasting theories of ethical and economic value, the role of narrative in ethical theory and pedagogy, and the associative powers of music to show how the lyrics and music of songs might help classroom learning resonate later in life. In doing so, the essay shows how the songs of rebellious rock musicians might unsettle stereotypical conceptions of business and resettle appreciation for the value of the arts and humanities in life and work.